2018
DOI: 10.1111/jog.13747
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial DNA copy number, cytochrome c oxidase activity and reactive oxygen species level in metaphase II oocytes obtained from in vitro culture of cryopreserved ovarian tissue in comparison with in vivo‐obtained oocyte

Abstract: This study showed that a two-step in vitro culture of mouse ovarian tissue decreased the mtDNA copy number and cytochrome c oxidase activity of metaphase II oocytes through an increase in their ROS level in comparison with in vivo-obtained oocytes. Thus, the in vitro culture methods should be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
2
6
2
Order By: Relevance
“…In contrast to our results, Amoushahi, Salehnia, and Ghorbanmehr (2018) showed that oocytes matured in vitro displayed lower mtDNA copy number of those matured in vivo. These controversies may be due to the difference in species and techniques for determining the mtDNA copy number in oocytes.…”
Section: Ivm Oocytes Exhibit Increased Mtdna Copy Number Probably Bcontrasting
confidence: 99%
“…In contrast to our results, Amoushahi, Salehnia, and Ghorbanmehr (2018) showed that oocytes matured in vitro displayed lower mtDNA copy number of those matured in vivo. These controversies may be due to the difference in species and techniques for determining the mtDNA copy number in oocytes.…”
Section: Ivm Oocytes Exhibit Increased Mtdna Copy Number Probably Bcontrasting
confidence: 99%
“…The results of the present study are in line with previous studies that showed SS can be considered as an effective factor in the oocyte maturation and the rates of developmental parameters of in vitro cultured oocytes treated with SS increased significantly compared to the oocytes cultured in the medium without SS 13 , 25 . The similar effects of SS supplement in the culture medium on the development of follicle and oocyte in some mammal species have also been previously reported 23 , 26 , 28 31 . The obtained results may be related to the antioxidant properties of SS by reducing the ROS 13 , 26 , 28 31 .…”
Section: Discussionsupporting
confidence: 84%
“…It has also been shown that Sodium Selenite (SS) as a non-enzymatic antioxidant improves development of follicles, oocyte and embryo by elevating the total antioxidant capacity and reducing the level of ROS 13 , 23 26 . In our previous studies, it was shown that adding SS to the oocyte maturation media increased mtDNA content of the oocytes 13 , 26 . This study was designed to bring some additional information regarding the effect of SS on the biogenesis of oocyte mitochondria through TFAM expression.…”
Section: Introductionmentioning
confidence: 99%
“…Although the high efficiency of energy production in mitochondria via oxidative phosphorylation pathway, it is considered as a main source of ROS. High levels of ROS lead to cell apoptosis through impairment of the mitochondrial activity in oocytes and embryos [38]. Internally produced or externally added antioxidants play important roles to maintain the oocyte’s oxidant/antioxidant balance during IVM.…”
Section: Discussionmentioning
confidence: 99%